Strain rate effects on characteristic stresses and acoustic emission properties of granite under quasi-static compression - Liu, Lu; Wang, Sijing; Yang, Wencheng (Frontiers in Earth Science, 2022)
In order to further investigate the strain rate effects on characteristic stresses and acoustic emission parameters of rock under quasi-static compression, uniaxial compressive tests were conducted on cylindrical specimens measuring 50 mm in diameter and 100 mm in height using a rock material testing machine and a multi-channel acoustic emission monitoring system at strain rates ranging from 10-6 s-1 to 10-2 s-1. The stress-strain curves of rock samples, characteristic stresses, energy data, and temporal and spatial distribution of acoustic emission signals were obtained and analyzed. The experimental results certified a linearly positive correlation between characteristic stresses and the logarithm of strain rates, despite the fact that the linear correlation varies for different characteristic stresses, whereas the ratios of characteristic stresses essentially do not change with increasing strain rates. The input energy and elastic strain energy at the damage point, UCS point and failure stress point exhibit a linearly positive correlation with the logarithm of strain rates when the strain rate exceeds 10-5 s-1. Meanwhile, the characteristics of energy conversion between input energy and elastic strain energy or the dissipated energy at different characteristic stresses points were explored. Based on this, the energy conversion process of rock under quasi-static compression can be divided into three stages: energy accumulation, energy dissipation, and energy release, respectively. Besides, it is noted that the total number of the located AE events decreases as strain rates increase when the strain rate exceeds 10-5 s-1, and the majority of located AE events occur during the crack closure stage and unstable crack growth stage. Finally, based on the perspective of energy conversion and the structural properties of multi-scale defects in rock, the mechanism of the increase of characteristic stresses with the increase of strain rates was proposed: that is, when rock is subjected to quasi-static compression, the higher strain rates can activate the small-scale defects, which necessitates more input energy from the external load via continuous work and causes an increase in the associated characteristic stresses.